2013
DOI: 10.1017/s0031182013001285
|View full text |Cite|
|
Sign up to set email alerts
|

Urban forests as hubs for novel zoonosis: blood meal analysis, seasonal variation inCulicoides(Diptera: Ceratopogonidae) vectors, and avian haemosporidians

Abstract: Culicoides vectors can transmit a diverse array of parasites and are globally distributed. We studied feeding preferences and seasonal variation of Culicoides (Diptera: Ceratopogonidae) vectors in an urban forest of Germany to determine whether humans living nearby are readily exposed to vector-borne parasites from wild animals. We used a fragment of the mtDNA COI gene to identify hosts from blood meals. We amplified a fragment of the mtDNA cyt b to detect haemosporidian infections in Culicoides abdomens and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 69 publications
3
29
1
1
Order By: Relevance
“…Moreover, phylogenetically related haemosporidian lineages (e.g., sister lineages) do not necessarily have a similar host breadth and geographic distribution [74], which challenges our ability to predict novel haemosporidian zoonoses. Taken together, the evidence on host distributions suggests that haemosporidian parasites have the potential to rapidly develop novel host-associations [19], but see [64]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, phylogenetically related haemosporidian lineages (e.g., sister lineages) do not necessarily have a similar host breadth and geographic distribution [74], which challenges our ability to predict novel haemosporidian zoonoses. Taken together, the evidence on host distributions suggests that haemosporidian parasites have the potential to rapidly develop novel host-associations [19], but see [64]. …”
Section: Resultsmentioning
confidence: 99%
“…Previous work suggests that different dipteran families are specialized in transmitting different Haemosporida genera [e.g., Ceratopogonidae transmit only Haemoproteus ( Parahaemoproteus ) parasites, [22,47]. Recent work on Culicidae [57-59] and Ceratopogonidae [18,19,60,61] shows that many vector species have broad feeding preferences, even across vertebrate classes. Thus, vectors may come in contact with a diverse array of Haemosporida parasites, including genera they do not normally transmit [e.g., [18,60,62-64].…”
Section: Discussionmentioning
confidence: 99%
“…All lineages identified here are known to infect both migratory and sedentary Passeriforms (Table 1 ), except DELURB5, which has, to date, only been sampled from a migratory bird, the common house martin ( Delichon urbicum ), in Spain [ 66 ]. Interestingly, the highest richness in terms of the number of lineages happens in the summer, coinciding with both the period of high vector abundance, a common pattern in haemosporidia [ 97 ], and with the breeding period of migratory birds in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing host-feeding patterns of blood-feeding dipterans can reveal vectors of zoonotic pathogens [50]. Our blood meal analysis revealed that all tested mosquito species feed upon humans, and Ma.…”
Section: Discussionmentioning
confidence: 99%